John Steinbeck - unknown:::Creator::::::::::::
From left to right: Beatrice Steinbeck, John Steinbeck, Gwyn Steinbeck, Stanford Steinbeck, Max de Vega, on the beach in Mexico. Postcard print.Original is in the safe.